Problems and Strategies of Teachers in the Application of the Merdeka Curriculum in Indonesian Language Learning at Madrasah Ibtidaiyah Al Fithrah Surabaya - Tuti Marlina; Soleha (STAI At-Tahdzib, 2025)
The application of the Merdeka curriculum in Indonesian language learning has become a complex and challenging topic. Although the Merdeka Curriculum aims to provide more freedom to teachers and students in determining learning methods and materials, there are various problems that arise in its implementation. This research aims to identify and analyze the problems faced in implementing the Merdeka Curriculum, especially in learning Indonesian. As well as solutions carried out by teachers in overcoming problems that occur in the Class 5C Madrasah Ibtidaiyah Al Fithrah Surabaya class. This research method uses a descriptive qualitative approach and data collection techniques using observation, interview and documentation. Data analysis is carried out through data collection, data reduction, data presentation, and drawing conclusions. The results of research on the implementation of the Merdeka curriculum at Madrasah Ibtidaiyah Al Fithrah Surabaya have started in stages since the 2022-2023 academic year and are going quite well even though there are obstacles such as students’ low interest in reading, poor understanding of vocabulary, and the inability to differentiate between standard language and internet language. The solutions implemented include getting students used to reading, choosing reading that they like but are educational, creating vocabulary learning media, as well as providing in-depth training and using technological media for contextual learning with regular evaluations.